Climate Toolkits for Infrastructure PPPs - World Bank (World Bank, Washington, DC, 2022)
The time for action to build a better future and green recovery has never been stronger as we navigate the uncertainty of a world attempting to manage its way out of a triple crisis: debt sustainability, climate change, and pandemic. The fiscal constraints of governments across the globe open the door to new opportunities and challenges to crowd in private sector solutions, innovation, and finance to create new solutions and pathways to meet Paris Agreement goals on climate change. Participation of the private sector in climate-smart investments and infrastructure is critical and public-private partnerships (PPPs) are among the key solutions. PPPs are critical because the public sector alone will not be able to fill in the infrastructure gap without mobilizing private sector expertise, innovative thinking, investment capacity, and finance. PPPs can be a challenge though, because climate change creates uncertainty and it is hard to play with uncertain moving pieces within the framework of PPPs, which require a certain degree of predictability to attract investment and finance. This toolkit aims to address this precise challenge by embedding a climate lens and approach into upstream PPP advisory work and structuring. If structured correctly, PPPs can increase climate resilience offering innovative solutions to address both mitigation and adaptation challenges. PPPs are able to provide well-informed and well-balanced risk allocation between partners offering long-term visibility and stability for the duration of a contract (often 25 or 30 years, sometimes even more), compensating climate change uncertainty through contractual predictability.